1988
DOI: 10.2190/w0vc-v1bw-wu54-cpq5
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy: Its Cost Burden and Barrier to Medical Care in a Drug-Oriented Health Care System

Abstract: In order to determine the economic and therapeutic implications of the prescriber habit in a drug-oriented health care system, data were collected on the provisional diagnosis, prescribed drugs, and their cost and procurement pattern among 1450 pediatric outpatients in a Nigerian University Teaching Hospital. It was found that on average, about five drugs were prescribed for each patient, and there was a tendency to prescribe more expensive and sometimes unnecessary drugs. The more the number or higher the cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…This practice needs to be reduced because it can cause economic burden on patients as well as it increases the risk of adverse drug reactions and drug interactions. [12][13][14] According to our study, from Table 8 we infer that an overwhelming majority of the patients were prescribed ACEIs alone (19%), among the drug combinations prescribed ACEIs and calcium channel blockers combination was frequently prescribed (9%). This reiterates the view from many studies which state the role of ACEIs as first choice drugs in the treatment of diabetic-hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…This practice needs to be reduced because it can cause economic burden on patients as well as it increases the risk of adverse drug reactions and drug interactions. [12][13][14] According to our study, from Table 8 we infer that an overwhelming majority of the patients were prescribed ACEIs alone (19%), among the drug combinations prescribed ACEIs and calcium channel blockers combination was frequently prescribed (9%). This reiterates the view from many studies which state the role of ACEIs as first choice drugs in the treatment of diabetic-hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…A quarter of the world's population is concentrated in developing countries and has access to only a small proportion of the world's drug production [1]. In spite of the above stated facts, irrational prescriptions and use of drugs has for long been known to be a feature of health care settings of developing countries, and is characterized by polypharmacy, excessive use of antibiotics and injections and use of drugs of doubtful efficacy [4,5]. This practice undermines the articulate efforts of drug supply systems and the provision of good quality health care with the meagre resources allocated to the health care sector in these countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, field surveys carried out in many of these countries have highlighted a significant degree of inappropriate use of drugs in their health care facilities 3 . Studies by Hogerzeil and his colleagues, and in Nigeria, have shown that there is a high rate of polypharmacy, overuse of antibiotics and injections and use of drugs with unproven efficacy [4][5][6][7] . Inappropriate prescribing is known all over the world as a major problem of health care delivery; in Nigeria, this has compounded the efficient and ever increasing cost of health care delivery.…”
Section: Introductionmentioning
confidence: 99%